Pharmacological Interventions for Bacterial Prostatitis - Xiong, Situ; Liu, Xiaoqiang; Deng, Wen; Zhou, Zhengtao; Li, Yulei; Tu, Yechao; Chen, Luyao; Wang, Gongxian; Fu, Bin (Frontiers in Pharmacology, 2020)
Prostatitis is a common urinary tract condition but bring innumerable trouble to clinicians in treatment, as well as great financial burden to patients and the society. Bacterial prostatitis (acute bacterial prostatitis plus chronic bacterial prostatitis) accounting for approximately 20% among all prostatitis have made the urological clinics complain about the genital and urinary systems all over the world. The international challenges of antibacterial treatment (emergence of multidrug-resistant bacteria, extended-spectrum beta-lactamase-producing bacteria, bacterial biofilms production and the shift in bacterial etiology) and the transformation of therapeutic strategy for classic therapy have attracted worldwide attention. To the best of our knowledge currently, there is not a single comprehensive review, which can completely elaborate these important topics and the corresponding treatment strategy in an effective way. This review summarizes the general treatment choices for bacterial prostatitis also provides the alternative pharmacological therapies for those patients resistant or intolerant to general treatment.